THE RISK OF THERAPY-RELATED MYELODYSPLASIA/ACUTE MYELOID LEUKEMIA IN HODGKIN LYMPHOMA HAS SUBSTANTIALLY DECREASED IN THE ABVD ERA ABOLISHING MECHLORETHAMINE AND PROCARBAZINE AND LIMITING VOLUMES AND DOSES OF RADIOTHERAPY - Brusamolino, Ercole; Gotti, Manuel; Fiaccadori, Valeria (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
Patients with Hodgkin lymphoma treated with DNA-breaking alkylating agents such as mechlorethamine and procarbazine in the MOPP regimen and with topoisomerase II inhibitors, such as etoposide did show a long-term risk of developing therapy-related myelodysplasia and acute myelogenous leukaemia (MDS/AML). With the introduction of the ABVD (adriamycin, bleomycin, vinblastine, dacarbazine) regimen, this risk has substantially been reduced. In this review, different experiences are discussed to determine whether and how modifications of treatment in different cohorts of patients have reduced the overall risk of secondary MDS/AML. These data are drawn from large cohorts of patients treated over time with different therapies with an adequate follow-up.